Enhancing Reading Comprehension Among Students With High-Functioning Autism Spectrum Disorder: A Randomized Pilot Study - Roux, Catherine; Dion, Eric; Barrette, Anne (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
Reading with comprehension is a challenge for students with high-functioning autism spectrum disorder. Unfortunately, research has little to offer to teachers trying to help these students. The present study pilots a new intervention targeting vocabulary, main idea identification, anaphoric relations, and text structure. Students (N = 13, M age = 9 years) were randomly assigned to either a control or an intervention condition. Descriptive analyses suggest that the intervention is effective; compared with their control condition peers, students in the intervention condition apparently made more progress on the vocabulary, main idea identification, and comprehension measures.